The effect of vitamin D supplementation on glycemic control in diabetic vitamin D deficient pregnant women - Nangia, Sangita; Lalnunpuii (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: This study aimed to evaluate the effect of vitamin D supplementation on glycemic control in diabetic vitamin D-deficient pregnant women and assess the fetomaternal outcomes and compare the fetomaternal outcomes between vitamin D-supplemented and non-supplemented diabetic pregnant women. Methods: A hospital-based case-control study was conducted at Kasturba Hospital, Delhi, involving 60 pregnant women diagnosed with gestational diabetes mellitus (GDM) or overt diabetes. Participants were randomized into two groups: one receiving weekly vitamin D3 supplementation (60,000 IU) until delivery and a control group receiving routine antenatal care without vitamin D supplementation. Glycemic parameters, oral hypoglycaemic agent and insulin requirements, and maternal-fetal outcomes were assessed. Maternal outcomes included pre-eclampsia, fetal growth restriction, liquor amount, mode of delivery and fetal outcomes included birth weight, neonatal intensive care unit (NICU) admissions, and neonatal hypoglycaemia. Statistical analysis was carried out using statistical packages for IBM statistical package for the social sciences (SPSS) versus 22 for Windows. Two sided p values was considered as statistically significant at p<0.05. Results: With vitamin D supplementation, improved glycemic control was observed in pregnant women with diabetes with a mean change of fasting blood sugar 21.45 (SD=15.99) in the supplemented group compared to 8.37 (SD=9.88) in the controls with p value <0.001 and the mean change of post prandial blood sugar was 39.13 (SD=41.33) in the supplemented group while the control group had a mean change of 8.93 (SD=40.99) with a p value of 0.006. However, vitamin D supplementation does not change the maternal and fetal outcomes of pregnancy in diabetic mothers. Conclusions: Vitamin D supplementation in diabetic vitamin D-deficient pregnant women improved glycemic control. Universal supplementation is recommended for all diabetic pregnant women along with adequate sun exposure and consumption of vitamin D rich foods.